INTEGRATING CONSERVATION EDUCATION IN BIOLOGY: COMMUNITY AWARENESS OF LONG-TAILED MACAQUE CONSERVATION - Satianugraha, Haruji; Prianto, Agus (Universitas Lancang Kuning, 2025)
Ecosystem degradation and biodiversity loss in Indonesia are often driven by a lack of public awareness regarding conservation. One species significantly affected is the long-tailed macaque (Macaca fascicularis), whose population is threatened by habitat changes and human interactions. This study aims to compare the conservation awareness of communities in Babakan Subdistrict (Plangon), Cirebon, and Purwasari Village, Kuningan, to support conservation education integration into Biology learning. A quantitative descriptive method with a survey technique was used, collecting data through validated and reliable questionnaires. The respondents consisted of 40 individuals from each research location. Data analysis was conducted using the Mann-Whitney U test to examine differences in conservation understanding between the two communities. The findings revealed significant differences, with the Babakan Subdistrict (Plangon) community exhibiting a higher level of conservation awareness than the Purwasari Village community. This difference is likely influenced by Plangon's role as an educational tourism site, which indirectly enhances conservation awareness. The study concludes that conservation understanding can be improved through educational programs integrated into Biology learning and community activities. Therefore, it is recommended to implement more intensive and collaborative conservation education programs at the community, school, and local government levels to enhance environmental awareness